(untitled) (Web of Teachers: Inderscience Research, 2025)
Mahmudkhoja Behbudi (1875–1919) was a prominent intellectual, journalist, and reformer who played a crucial role in the development of modern journalism in Central Asia. As a leading figure in the Jadid movement, he used the press to advocate for education, enlightenment, and national awakening. His newspaper Oina (1913–1915) became a platform for discussing socio-political issues, modern education, and women’s rights. Behbudi’s writings emphasized the necessity of reforming the traditional education system and encouraged the establishment of usul-i jadid schools. Despite facing censorship and political suppression, his contributions significantly shaped Turkestan’s intellectual landscape. His legacy continues to inspire scholars and journalists advocating for freedom of thought and social progress in the region.